The Effect of Differentiated Instruction on Eleventh Grade Students’ Narrative Writing Skill at SMA Budi Murni 2 - Maria Sihotang; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Jurnal Pendidikan Indonesia, 2026)
This study aims to determine the effect of Differentiated Instruction on students' narrative text writing ability. In this study, there are two variables used, namely Differentiated Instruction as the independent variable and students' narrative text writing ability as the dependent variable. This study was conducted at SMA Budi Murni 2 Medan on eleventh grade students in the 2025/2026 Academic Year. The population of this study was eleventh grade students of SMA Budi Murni 2 Medan, while the research sample consisted of two classes selected by purposive sampling technique, namely eleventh grade students 3 as the experimental class and eleventh grade students 2 as the control class. This study used a quasi-experimental method with a pre-test and post-test control group design. Data were collected through writing tests before and after treatment. The results of the study showed that the narrative text writing ability of students taught using Differentiated Instruction experienced a better improvement compared to students taught using conventional methods. The average score of the experimental class increased from 61.94 in the pre-test to 76.39 in the post-test, while the average score of the control class increased from 58.19 to 66.39. The implementation of Differentiated Instruction is one of the solutions to improve students' writing skills because learning is adjusted to students' learning readiness, interests, and learning profiles so that they are more actively involved in the learning process. Therefore, it can be concluded that Differentiated Instruction is effective in improving the narrative text writing skills of eleventh-grade students of SMA Budi Murni 2 Medan